A Culturally and Linguistically Appropriate Telephone Support Intervention for Diverse Family Caregivers of Persons With Dementia During the COVID-19 Pandemic. (August 2022) - Lee, Jung-Ah; Kim, Hyun Jung; Ju, Eunae; Guo, Yuqing; Rousseau, Julie; Gibbs, Lisa; Tran, Tiffany Marie; Tom, Courtney Elizabeth; Sabino-Laughlin, Eilleen; Kehoe, Priscilla
Caregivers of persons with dementia (PWDs) were socially isolated with little support during the COVID-19 pandemic "Stay-At-Home" order in the United States. To enhance social and emotional connection for diverse caregivers, a culturally/linguistically appropriate telephone intervention provided compassionate listening, mindful breathing, and COVID-19 safety education. The study purpose was to understand caregiving challenges and to evaluate the intervention for caregivers during the early pandemic using a qualitative approach. Twenty-three caregivers participated in the intervention provided by bilingual research assistants for 3 months. Call logs were used to describe the caregivers' dialogue. Thematic analysis identified (a) the challenges, including fear of coronavirus disease, providing around-the-clock care, and forced isolation and negative emotions; and (b) caregivers' experience with the intervention, including connecting with the outside, relief from emotional stress, reliable COVID-19 information, and reinformed caregiving skills. Results suggest that the telephone support was of benefit to diverse caregivers of PWDs during the pandemic by promoting social connection and reducing emotional distress.